Experimental study on devolatilization characteristics of lignite during pressurized oxy-fuel combustion: Effects of CO2 and H2O. (1st January 2023) - Geng, Chenchen; Zhong, Wenqi; Bian, Zhoufeng; Liu, Xuejiao
Graphical abstract: Highlights: Pressurized devolatilization characteristics of lignite are investigated. Combined effects of CO2 /H2 O present addition, synergy, and inhibition interactions. Pathways of CO2 /H2 O involved in physicochemical structure evolution are different. Interactive mechanisms of CO2 /H2 O are dependent on char pore structure evolution. Chemical structures dominate oxy-fuel combustion reactivities of chars. Abstract: Pressurized oxy-fuel combustion (POFC) is currently considered one of the advanced coal utilization technologies for large-scale CO2 capture but causes distinct coal conversion behavior, particularly more complicated and unclear with wet recycle. To explore coal conversion mechanisms and structural evolution of chars during the initial stage of POFC, lignite devolatilization was conducted in an isothermal horizontal tube furnace at 900 °C in individual and blending CO2 and H2 O atmospheres (CO2 /N2, H2 O/N2, and H2 O/CO2 ) under different pressures of 0.1 to 0.9 Mpa. The pore and chemical structures of resulting chars were characterized using N2 adsorption and Raman spectroscopy, and oxy-fuel combustion reactivities of chars were evaluated by thermogravimetry. The results indicate that coal char conversion in coexisting H2 O/CO2 presents three different interactions of addition, synergy, and inhibition, corresponding to mesoporous surface area evolution of chars with partial and total pressures of H2 O. CO2 chars primarily consist of micropores while chars formed in H2 O-rich atmospheres contain more mesopores. These dominant micro-/mesopore numbers increase with CO2 /H2 O concentrations but decrease at 0.9 Mpa. The accelerated condensation of aromatic rings in chars induced by CO2 and H2 O gasification also follows different pathways. H2 O gasification dominates the carbon skeleton structure evolution of H2 O/CO2 chars but the interaction between H2 O/CO2 results in the complex variations of O-containing structures. CO2 /N2 chars have the highest oxy-fuel combustion reactivities, follow by H2 O/CO2 chars, and H2 O/N2 char reactivities are the lowest. The combustion reactivities of H2 O/CO2 chars show a more obvious attenuation trend than that of H2 O/N2 chars and the disparities narrow with H2 O concentration. Elevated total pressure decreases the reactivities of all chars along with the growth of aromatic ring sizes. The correlations between oxy-combustion reactivities and Raman band area ratios highlight the significance of the devolatilization stage to subsequent char combustion.